Case study: Kuaci Bakar Padu Letopz / Arif Hakimi Abdul Hafiz ... [et al.] - Abdul Hafiz, Arif Hakimi; M. Jamaluddin, Muhammad Ariff Adruse; Juah, Natasha Stephanie; Mohd Seddikin, Nurafikah Shamimi; Azmi, Siti Hajar (2021)
A case study is a description of an action, event, or problem that incorporates a genuine or fictional circumstance as well as the complications you'd face in the workplace. Case studies are used to demonstrate how real-life complications influence decisions. Acase study is also a method of analysis as well as a specific research methodology for studying a subject. Analyzing a case study challenges you to put your knowledge and thinking skills to the test in a real-life situation. For this written report, we have chosen Kuaci Bakar Padu Letopz for our case study. Kuaci Bakar Padu Letopz is small local business owned by Muhammad Saifuddin bin Che Othman situated in Sri Petaling, Malaysia. After completing an assignment for his degree entrepreneur subject, ENT530, he began the business in 2019. He spotted an opportunity in his business and began to grow it online from the comfort of his own home. To market the product, he used Shopee (a shopping program). He also uses social media platforms like Instagram and Facebook to promote Kuaci Bakar Padu Letopz. This modest business became his side income in addition to his main job as HR/Admin Executive for the Malaysian Ministry of Health.